Superior Specimen and Diagnostic Accuracy with Endoscopic Ultrasound-Guided Liver Biopsies Using 19-Gauge versus 22-Gauge Core Needles - Rucha M. Shah; Jason Schmidt; Elizabeth John; Sheila Rastegari; Priyanka Acharya; Prashant Kedia (Korean Society of Gastrointestinal Endoscopy, 2021)
Background/Aims Endoscopic ultrasound-guided liver biopsy (EUS-LB) is an effective and safe method of procuring liver tissue. The aims of this study were to assess and compare the outcomes and tissue adequacy of a single-pass, single-actuation, wet suction technique between 19 G and 22 G needles in patients undergoing EUS-LB. Methods We performed a prospective case series study of 20 patients undergoing EUS-LB at a single center between September 2017 and April 2020. The primary objective was to evaluate differences in sample adequacy via a single actuation wet suction technique between a 19 G core needle and a 22 G core needle. Adequacy was gauged by cumulative core biopsy length and the number of portal tracts visualized. Results The 19 G needle provided a longer core length (2.5 cm vs. 1.2 cm, p<0.0001), more complete portal tracts (5.8 vs. 1.7, p<0.0001), more total tracts (8.8 vs. 3, p<0.0001), and a longer, intact, fragment length (0.75 cm vs. 0.32 cm, p<0.0006). The 19 G needle was superior in providing adequate (60% vs. 5%, p<0.001) and diagnostic pathologic samples (85% vs. 10%, p<0.001). Conclusions A single-pass, single-actuation, wet suction technique using a 19 G needle is superior to that using a 22 G needle for tissue acquisition and sample adequacy in EUS-LB.